Revolutionizing cardiovascular research: Human organoids as a Beacon of hope for understanding and treating cardiovascular diseases - Jinli Li; Yang Li; Guangtao Song; Haiying Wang; Qing Zhang; Min Wang; Muxue Zhao; Bei Wang; HuiGuo Zhu; Liu Ranzhi; Qiang Wang; Yuyan Xiong (Materials Today Bio)
Organoids, exhibiting the capability to undergo differentiation in specific in vitro growth environments, have garnered significant attention in recent years due to their capacity to recapitulate human organs with resemblant in vivo structures and physiological functions. This groundbreaking technology offers a unique opportunity to study human diseases and address the limitations of traditional animal models. Cardiovascular diseases (CVDs), a leading cause of mortality worldwide, have spurred an increasing number of researchers to explore the great potential of human cardiovascular organoids for cardiovascular research. This review initiates by elaborating on the development and manufacture of human cardiovascular organoids, including cardiac organoids and blood vessel organoids. Next, we provide a comprehensive overview of their applications in modeling various cardiovascular disorders. Furthermore, we shed light on the prospects of cardiovascular organoids in CVDs therapy, and unfold an in-depth discussion of the current challenges of human cardiovascular organoids in the development and application for understanding and treating CVDs.